Moral and Cultural Values in the Story of Putri Pukes from Central Aceh - Astri Juraini; Dina Wulansari; Muhammad Abrar Muda; Dina Syarifah Nasution (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2022)
Princess Pukes is the small kingdom's beloved girl and the only child. Because she denied his mother, who said she should not look back when escorted to the groom's house before passing through the Pukes area. But because she couldn't stand her parents' choice, the princess accidentally looked back, suddenly lightning struck, and the rain was weighty. So Putri Pukes took shelter in the cave. Inside the cave, Putri Pukes stood in a corner because of her cold body temperature. Slowly the princess's body hardened and turned into stone. The prince who entered first heard the news that the princess had turned to stone. Enthusiastically, he prayed to be turned into stone. Ultimately, the love story between Princess Pukes and the prince ends tragically. This study aims to (1) describe the moral values ??in the Putri Pukes folklore, (2) describe the cultural values ??in the Putri Pukes folklore, and the source of the data taken is the Putri Pukes folklore. The results of this study aim to be an example for the younger generation and to have an extensive and positive influence, especially on those who have read this story, so as not to imitate the wrong attitude of the Pukes daughter, who violates the message of her parents. However, to reduce incidents like this, always teach other younger generations to obey and listen to their parents' messages to get good right from Allah SWT.